Oriental Style and Asian Chic: The Politics of Racial Visibility in Film and Fashion - Choo, Hee-Jung Serenity (American Studies, 2012)
This essay reviews Yellow Future: Oriental Style in Hollywood Cinema by Jane Chi Hyun Park; and The Beautiful Generation: Asian Americans and the Cultural Economy of Fashion, by Thuy Linh Nguyen Tu.